Temperature dependence of nitrate reductase in the psychrophilic unicellular alga Koliella antarctica and the mesophilic alga Chlorella sorokiniana - DI MARTINO RIGANO VITTORIA; VONA VINCENZA; LOBOSCO ORNELLA; CARILLO PETRONIA; LUNN JOHN EDWARD; CARFAGNA SIMONA; ESPOSITO SERGIO; CAIAZZO MARIANNA; RIGANO CARMELO (Plant, Cell and Environment, 2006)
Temperature responses of nitrate reductase (NR) were studied in the psychrophilic unicellular alga, Koliella antarctica, and in the mesophilic species, Chlorella sorokiniana. Enzymes from both species were purified to near homogeneity by Blue Sepharose (Pharmacia, Uppsala, Sweden) affinity chromatography and high-resolution anion-exchange chromatography (MonoQ; Pharmacia; Uppsala, Sweden). Both enzymes have a subunit molecular mass of 100 kDa, and K. antarctica NR has a native molecular mass of 367 kDa. NR from K. antarctica used both NADPH and NADH, whereas NR from C. sorokiniana used NADH only. Both NRs used reduced methyl viologen (MVH) or benzyl viologen (BVH). In crude extracts, maximal NADH and MVH-dependent activities of cryophilic NR were found at 15 and 35°C, respectively, and retained 77 and 62% of maximal activity, respectively, at 10°C. Maximal NADH and MVH-dependent activities of mesophilic NR, however, were found at 25 and 45°C, respectively, with only 33 and 23% of maximal activities being retained at 10°C. In presence of 2 μ m flavin adenine dinucleotide (FAD), activities of cryophilic NADH:NR and mesophilic NADH:NR were stable up to 25 and 35°C, respectively. Arrhenius plots constructed with cryophilic and mesophilic MVH:NR rate constants, in both presence or absence of FAD, showed break points at 15 and 25°C, respectively. Essentially, similar results were obtained for purified enzymes and for activities measured in crude extracts. Factors by which the rate increases by raising temperature 10°C (Q10) and apparent activation energy (Ea) values for NADH and MVH activities measured in enzyme preparations without added FAD differed slightly from those measured with FAD. Overall thermal features of the NADH and MVH activities of the cryophilic NR, including optimal temperatures, heat inactivation (with/without added FAD) and break-point temperature in Arrhenius plots, are all shifted by about 10°C towards lower temperatures than those of the mesophilic enzyme. Transfer of electrons from NADH to ...